OP0061 CONSUMER PERSPECTIVE ON PAEDIATRIC RHEUMATOLOGY CARE AND SERVICE DELIVERY: RESULTS FROM AN EARLY JUVENILE IDIOPATHIC ARTHRITIS (JIA) COHORT STUDY. (June 2019) - Heinrich, Michaela; Klotsche, Jens; Sengler, Claudia; Niewerth, Martina; Weller-Heinemann, Frank; Haas, Peter; Horneff, Gerd; Hospach, Toni; Moenkemoeller, Kirsten; Thon, Angelika; Foeldvari, Ivan; Minden, Kirsten
Abstract : Background: Timely access to specialized and multidisciplinary care is a core principle in the management of JIA patients and crucial to achieve the best possible outcome for children and adolescents with JIA. Objectives: To assess satisfaction with access to specialized care and used health care services of families with children with JIA and to identify factors associated with unmet needs. Methods: Parents of JIA patients enrolled in the early JIA cohort study ICON completed the Child Healthcare Questionnaire on Satisfaction, Utilisation and Needs (CHC-SUN) 1 and the Family Burden Questionnaire (FaBel) 3 months after enrolment. The socioeconomic status, disease activity, patients' functional ability and quality of life were also assessed. Factors associated with unmet needs were identified by logistic regression analysis. Results: Data were available from 835 families with children diagnosed with JIA 3 months (median, IQR 1-6) after symptom onset and cared for by paediatric rheumatologists (68% females). At assessment (4.6 months after diagnosis, median), 67% of patients received non-steroidal anti-inflammatory drugs, 50% received conventional synthetic DMARDs and 8% biologic DMARDs. In addition, the following health care services were utilized: 84% physiotherapy, 23% occupational therapy, 21% supply with physical aids, 17% telephone counselling, 15% health education, 13% social worker services, and 11% psychological counselling. Unmet needs were most frequently reported for health education (19%), rehabilitation services (11%), psychological counselling (11%), self-help groups (10%), and lowest for physiotherapy (2%). Unmet needs varied depending on the type of service and JIA category (Table). They were more frequently observed in families with higher burden as indicated by FaBel, but were not associated with migration background and socioeconomic status. Most parents were generally satisfied with their child's health care (satisfied 30%, very satisfied 42%, extremely satisfied 23%). Satisfaction was highest with the behaviour of doctors and lowest with school-related services (e.g. 36% not or partly satisfied with teachers' knowledge about the child's illness) and diagnosis/information (e.g. 29% not or partly satisfied with the time required for the diagnosis). Conclusion: There are, although infrequently, unmet needs and dissatisfaction with health services among families with children who have JIA and receive specialized care. Whether these deficits are relevant for long-term JIA outcomes will be further investigated in the ICON study. Reference: [1] Schmidt S, Thyen U, Chaplin J, Mueller-Godeffroy E; European DISABKIDS Group. Cross-cultural development of a child health care questionnaire on satisfaction, utilization, and needs. Ambul Pediatr. 2007;7:374-82. Acknowledgement: Funding by Federal Ministry of Research: 01 ER 1504A Disclosure of Interests: Michaela Heinrich: None declared, Jens Klotsche: None declared, Claudia Sengler: None declared, Martina Niewerth: None declared, Frank Weller-Heinemann: None declared, Peter Haas Grant/research support from: Pfizer, Gerd Horneff: None declared, Toni Hospach Speakers bureau: Chugai, Roche, Novartis, Kirsten Moenkemoeller: None declared, Angelika Thon: None declared, Ivan Foeldvari Consultant for: Chugai, Novartis, Kirsten Minden Consultant for: AbbVie